Effect of Vermicompost Enriched With Rock Phosphate on Cowpea - Sailajakumari S (Department Of Soil Science And Agricultural Chemistry,College Of Agriculture, 1999)
An investigation was carried out at the College of Agriculture, Vellayani during 1998 to evaluate the effect of vermicompost enriched with RP on P availability yield and quality of cowpea and the feasibility of reducing the inorganic P. The variety used was Kanakamoni. All the growth characters, yield and yield attributes studied were significantly influenced by different treatments. Nodule number per plant, weight of nodules per plant and root shoot ratio were maximum by the application of enriched vermicompost. Yield attributes like number of pods per plant, number of seeds per pod and hundred seed weight and total grain yield were significantly increased by the application of enriched vermicompost. Vermicompost primed with full RP or with half RP produced no significant difference in grain yield. Thus the results revealed that inorganic phosphoate for cowpea coufd be reduced to half• of its recommended dose by priming vermicompost with RP. Analysis of plant samples at harvest showed that maximum content of macronutrients except Mg was recorded by enriched vermicompost. It showed its superiority over other treatments for protein and P content of grain. Enriched vermicompost also registered significant increase in soil available N, P and K after the experiment.